2021
DOI: 10.3390/math9151814
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Solving Addition Problems Using Modified Schema-Based Instruction in Students with Intellectual Disabilities

Abstract: A study is presented on the strategies employed to solve additive change problems by three students with intellectual disabilities (two of them with autism spectrum disorder). The students followed a program involving modified schema-based instruction. The results show an improvement in the problem-solving skills of the three students, who achieved successful formal strategies associated with identifying the operation. We analyze the importance of adapting and/or emphasizing certain steps in the instruction pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…This confirms other studies that have shown that children with mathematics disabilities had difficulty comparing Arabic digits (i.e., symbolic number magnitude), but not comparing collections (i.e., non-symbolic number magnitude) (Rousselle & Noël, 2007). More generally, the benefits of using concrete manipulatives during instruction coincide with previous research on teaching arithmetic operations to students with learning difficulties (Baroody & Tiilikainen, 2003), and specifically with ASD (Bruno et al, 2021;Hart & Cleary, 2015;Polo-Blanco et al, 2019;. The use of sequences based on augmentative language to teach strategies to students with this disorder also proved beneficial, as other studies show (Hart & Cleary, 2015;Mirenda, 2003).…”
Section: Discussionsupporting
confidence: 89%
“…This confirms other studies that have shown that children with mathematics disabilities had difficulty comparing Arabic digits (i.e., symbolic number magnitude), but not comparing collections (i.e., non-symbolic number magnitude) (Rousselle & Noël, 2007). More generally, the benefits of using concrete manipulatives during instruction coincide with previous research on teaching arithmetic operations to students with learning difficulties (Baroody & Tiilikainen, 2003), and specifically with ASD (Bruno et al, 2021;Hart & Cleary, 2015;Polo-Blanco et al, 2019;. The use of sequences based on augmentative language to teach strategies to students with this disorder also proved beneficial, as other studies show (Hart & Cleary, 2015;Mirenda, 2003).…”
Section: Discussionsupporting
confidence: 89%
“…Some studies have already shown that the strategies and representations used by ASD children are variables that determine their performance (Bruno et al, 2021 ; Polo Blanco et al, 2021 ; Polo-Blanco & González-López, 2021 ; Polo-Blanco et al, 2022 ). Others have shown that some of the cognitive traits intrinsic to the disorder, such as low executive functioning profile, can directly interfere with mathematical performance and with implementing the actions that are needed to solve mathematical problems (Bull & Scerif, 2001 ; Kim & Cameron, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interventions should also consider stimulating the cognitive functions involved in mathematical problem solving that are most affected in ASD population (cognitive flexibility, inhibition, ToM and verbal comprehension) (Westby & Robinson, 2014 ; Whalon & Cox, 2020 ). Some evidence-based strategies for children with learning difficulties, such as Schema Based Instruction (SBI) (Fuchs et al, 2004 ) or the Conceptual Model-Based Problem Solving (COMPS) approach (Xin, 2018 ), have been successfully adapted to ASD children’ characteristics improving their ability to solve mathematical problems (Bruno et al, 2021 ; García Moya et al, 2022 ; Polo-Blanco & González-López, 2021 ; Polo-Blanco et al, 2021 , 2022 ; Root et al, 2017 ). Future empirical studies are needed to measure the effects of these adaptations on the development of some of the cognitive functions with lower scores found in ASD children.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is recognized that students with ID may experience greater challenges with mathematics as compared to their chronological age-matched students (Brankaer et al, 2011; Hoard et al, 1999). Several studies indicate that students with intellectual disability often lack basic mathematics skills (e.g., numerical magnitude comparison, measurement concept, and arithmetic operations) and higher order skills (e.g., mathematics problem-solving) (Brankaer et al, 2013; Browder et al, 2018; Bruno et al, 2021; Celik and Varun 2014; Clark et al,2016). These findings highlight the need for exploring effective interventions to teach mathematics to individuals with ASD and/or ID.…”
Section: Introductionmentioning
confidence: 99%